2015
DOI: 10.1176/appi.ajp.2015.14091100
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Mortality After Infection Among Persons With Severe Mental Illness: A Population-Based Cohort Study in Denmark

Abstract: Persons with severe mental illness have a markedly elevated 30-day mortality after infection. Some of these excess deaths may be prevented by offering individualized and targeted interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Thus, the analyses including metastatic stage should be interpreted with caution. In addition, the registration of cause of death in women with SMI in our study could also be subject to differential misclassification caused by expected higher rates of death from external causes, cardiovascular disease, diabetes, or infections in persons with SMI [ 2 , 23 , 35 ]. Further, some important clinical information, such as life style factors (e.g., smoking, physical inactivity, and high BMI) generally associated with SMI [ 8 , 36 ] and poorer prognosis after breast cancer [ 30 , 37 , 38 ], was not included in our analyses due to unavailability in the registers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the analyses including metastatic stage should be interpreted with caution. In addition, the registration of cause of death in women with SMI in our study could also be subject to differential misclassification caused by expected higher rates of death from external causes, cardiovascular disease, diabetes, or infections in persons with SMI [ 2 , 23 , 35 ]. Further, some important clinical information, such as life style factors (e.g., smoking, physical inactivity, and high BMI) generally associated with SMI [ 8 , 36 ] and poorer prognosis after breast cancer [ 30 , 37 , 38 ], was not included in our analyses due to unavailability in the registers.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with bipolar or psychotic disorder had 52% increased mortality risk within 30 days after their infection. 14 We could not find any study that explicitly explored risk factors associated with death from respiratory infections in individuals with SMD. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in deaths with conditions or causes in addition to COVID-19, there were on average 2.6 additional conditions or causes per death.…”
Section: Anmentioning
confidence: 98%
“…Several other examples of epidemiological studies exist, where mood and psychotic disorders are amalgamated in similar ways. 3,14,41,[45][46][47] Here, we combined psychotic and bipolar disorders into one category because the prevalence for somatic comorbidities and excess mortality are similar for both conditions. 1,2 We did not include severe depression in our SMD variable, since severe depression is a more heterogenous group.…”
Section: Limitationsmentioning
confidence: 99%
“…Prior research linked early childhood pneumonia with adverse long-term health problems like decreased lung function and chronic obstructive pulmonary disease (Svanes et al 2010) (Gray et al 2017) (de Marco et al 2011). Several other studies demonstrated that infections can lead to cognitive impairment (Leibovici 2013)(Benros et al 2015. Accelerated physical aging and an elevated risk of death by suicide associated with infections has also been suggested (Gavazzi & Krause 2002) (Lund-S ørens en et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding schizophrenia, an ample body of evidence indicates that infections are generally associated with high frequency of adverse events in this group of patients. First, infections account for leading causes of premature death in schizophrenia (Ribe et al 2015) (John et al 2018) (Brown et al 2010) (Saha et al 2007).…”
Section: Introductionmentioning
confidence: 99%